مقارنة بين أثر استخدام الطريقة الاستقرائية و الطريقة القياسية فى تدريس وحدة القرآن الكريم وأحمكام التجويد لطلبة الصف السابع الأساسى على التحصيل الفورى والمؤجل - مومنى، شحادة احمد الشحادة (: كلية تربية : جامعة اردنية, 1990)
Comparing the effect of the inductive and deductive methods in teaching a unit of the Holy Kora'an and tajweed (improved recitation) rules on the immediate and delayed achievement of the sevent graders